Illusion town ebook - Castle, Jayne (Harmony, 2016)
A new adventure begins on Harmony…    With its opulent casinos and hotels, the desert city of Illusion Town is totally unique—and will take you on a thrill ride you’ll never forget.   Hannah West isn’t the first woman to wake up in Illusion Town married to a man she barely knows, but she has no memory of the ceremony at all. For that matter, neither does Elias Coppersmith, her new husband. All either can remember is that they were on the run…   With Hannah’s dubious background and shaky para-psych profile, she could have done much worse. The cooly competent mining heir arouses her curiosity—as well as other parts of her mind and body. And even her dust bunny likes him.   But a honeymoon spent retracing their footsteps leads Hannah and Elias into the twisting underground catacombs, where secrets from both their pasts will come to light—and where the energy of their clashing auras will grow hot enough to burn…